Penggunaan Lampic Scheme untuk Meningkatkan Hasil Belajar Siswa SMP Negeri 2 Sigli pada Materi Sistem Peredaran Darah - Rahmi Agustina (Universitas Islam Negeri Ar-Raniry, 2015)
A classroom action research about the use of lampic Scheme to improve students’ learning outcomes and activity in learning sciences (IPA) on blood circulatory system concept has been conducted at SMP N 2 Sigli. It contributes to the development of science subjects and serves as a reference for the future research. This research was conducted in two cycles for three months. Students of class VIII-B were selected as the research subject. The data were collected by using test, observation, and questionnaire. The data were collected by measuring students’ learning outcomes from each meeting and also from observing students’ activities. The data were analyzed by using descriptive qualitative to find out the students’ mastery learning, the average score, the highest and the lowest score. To validate the data, they were verified quantitatively by putting them into the list of score. The research was conducted by implementing cycle of four stages: planning, implementing, observing, and reflecting. The results showed that there was an improvement in several aspects namely: The improvement of mastery learning in the first lesson was 37.50 %, while the second lesson was 59.37% with the average 43.75%. In the second cycle, the mastery learning of the first lesson was 59.37%, while the second lesson was 87.50% with the average 68.75%. The improvement was found both in students’ learning outcomes and activity.